Traffic Impact Analysis PT. Eastern Pearl Flour Mills – City Side Jl. Nusantara, Makassar - Hakzah, Hakzah; Azis, Azis; Andriyani, Andriyani; Yauri Yunus, Ahmad (ASTONJADRO, 2023)
PT. Eastern Pearl Flour Mills – City Side Makassar affects land use changes that have an impact on changes in traffic movement, so traffic impacts analysis is needed. The purpose of this study is to identify the performance of affected roads and intersections in the present and in the next 5 years, to handle traffic problems and conflicts by simulating models without handling (Do Nothing) and with handling (Do Something), analyzing time delays on the U-turns and modeling the origin-destination matrix using the Furness Method. This study uses qualitative and quantitative analysis methods that refer to the Manual Kapasitas Jalan Indonesia (MKJI, 1997) and The Furness method. The results of the analysis of the level of service on the Jl. The archipelago is in fairly good condition with LoS values A to B and DS 0.11 – 0.40 with a speed of 26.60 – 50.00 km/hour, the road performance that has the worst impact occurs at the Tol Reformasi – Jl. Nusantara with a projection for the next 5 years in 2027, where road performance has a LoS E and DS value of 0.88 with a delay time of 19 seconds/pcu. U-turn facility on Jl. Nusantara has an average delay time of 6.16 – 7.82 seconds for one rotating vehicle with a value of < 1 so that there is no queue. The results of the trip distribution analysis using The Furness model obtained the same value of generation and attraction in the second iteration, which means that it is still close to ideal conditions.